Smart Ports and Robotic Systems
XXXIV, 414 p. 41 illus., 30 illus. in color.
Keywords: This book provides a comprehensive overview of smart ports and remote technologies in the maritime industry. It demonstrates how modern advances in artificial intelligence and robotics have transformed the shipping industry, and assesses the impact of this technology from a law and governance standpoint. The book covers a range of topics including port autonomous operations systems, cybersecurity, big data analytics, digitalization and blockchain to throw light on the opportunities and benefits of these new technologies in improving security and safety. It also considers the challenges and threats of their application. It concludes by examining the trajectory of national and international regulatory developments. The book will appeal to scholars and students of maritime technology, law and governance, as well as practitioners and policymakers. Chapters 8, 19 and 20 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Tafsir Matin Johansson is Assistant Professor at the World Maritime University- Sasakawa Global Ocean Institute, Sweden. Dimitrios Dalaklis is Professor of Safety and Security at the World Maritime University, Sweden. Jonatan Echebarria Fernández is Honorary Lecturer at The City Law School, City, University of London, UK. Aspasia Pastra is Post-Doctoral Fellow at the World Maritime University- Sasakawa Global Ocean Institute, Sweden. Mitchell Lennan is Lecturer in Environmental Law at the University of Aberdeen, UK.